Pemanfaatan Daun Sirsak (Annona muricata L.) pada Media Umpan sebagai Pengendali Rayap Tanah (Coptotermes curvignathus Holmgren) - Farah Diba, Tri Eka Sari, Masnur Turnip, (Universitas Tanjungpura, 2014)
Soursop leaves (Annona muricata L.) function as repellent and anti feedant. The objective of this research was to identify the effect of usingsoursop leaves a botanical insecticide to control termites. This research was carried out in two laboratories in Tanjungpura University, Biology Laboratory, Faculty of Mathematics and Natural Sciences and Wood Technology Laboratory, Faculty of Forestry from Februari 2013 to May 2013. This Research utilised two factor, factorial design with completely randomized design (CRD).The first factor is the weight of soursop leaves ( 0 g, 2 g, 4 gand 6 g). The second is the types of bait media such as sawdust, filter paper, and ground termite nest. Each treatment was done three times to eventually achive thirty six experimental units. Subterranean termites highest morality is found in the combination of 6 grams of soursoup leaf powder 6 g with 10 g filter paper as the bait medium. The average morality of this termite is 99.33 %. On the other hand, the treatment resulted in the lowest weight lost of bait media is the combination of 4 grams of soursoup leaf powder with 10 grams of sawdust, losing averagely 9.99% of bait media weight.